Effects of snowfall depth on soil physical–chemical properties and soil microbial biomass in moss–dominated crusts in the Gurbantunggut Desert, Northern China - Zhao, Ruiming; Hui, Rong; Liu, Lichao; Xie, Min; An, Lizhe (Catena (Giessen), 2018)
Winter snowfall is an important source of moisture that may influence the growth and development of biological soil crusts (BSCs) in temperate desert regions of China. Yet there is still limited empirical knowledge about the effect of snowfall on BSCs. In this study, moss crusts from the Gurbantunggut Desert were exposed to five snow depths to evaluate how snowfall affected the physical–chemical properties (pH; electric conductivity, EC; soil organic carbon, SOC; total nitrogen, TN; available nitrogen, AN; available phosphorus, AP; available potassium, AK) and microbial biomass (soil microbial biomass carbon, SMBC; soil microbial biomass nitrogen, SMBN; soil microbial biomass phosphorus, SMBP) of soil in the BSCs, before (in October 2016: representing three consecutive years of snow manipulation) and after winter (in April 2017). Results showed that the soil water content increased significantly as snowfall depth increased (p < 0.05) in October 2016 and April 2017. Most of the soil physical–chemical features (EC, SOC, TN, AN, AP, and AK) and microbial biomass (SMBC and SMBN) showed an increase with an increase of snowfall depth after three consecutive years of snow manipulation. Moreover, for most experimental treatments, after a winter of melting snow (in April 2017) most of the soil properties were significantly higher (p < 0.05) than found in October 2016. Together, these results showed that the dynamics of soil nutrients and microbial biomass in moss BSCs were affected by snowfall depth in Gurbantunggut Desert. Different snowfall depths can have different effects on the dynamics of soil nutrients and microbial biomass of moss crusts, an impact that may alter the future growth and development of BSCs. Thus, we suggest that the potential influence of snowfall depth on soil nutrients and microbial biomass dynamics in BSCs require consideration when discussing the effects of moisture on ecological functions of BSCs in arid and semi–arid regions. •Snowfall depth change dynamic of soil nutrients in moss–dominated crusts.•Soil microbial biomass of moss–dominated crusts was influenced by snowfall depth.•Snowfall depth had more obvious influenced to soil in snowmelt period.•Snowfall depth may cause influence to ecological functions of moss–dominated crusts.